Relationship between human and his products in the environmental ethics aspect - Sztumski, Wiesław (Studia Ecologiae et Bioethicae, 2005)
The subject of ethics should not only be the valuation of different forms of human actions but also the evaluation of their results. Talking about the results of human activity, I mean not only the logical effects and consequences but also the material and spiritual products of our actions, that is different artefacts. It's impossible to include all the problems and evaluation of all the results of our actions. That is why I come down just to one issue - to the responsibility for the excessive intensity of human environment by the new technology products which are used as the assistance to human organism and mind. This type of responsibility fits environmental ethics which relates to the relation between human and the environment and this is why it is something new and wider in comparison with traditionally understood moral responsibility usually limited to the relation “ human - human”. The following issues are taken into consideration in this article: human in artefact environment, threats connected with the growth of artefacts in the area of spiritual culture, biological degradation of a man assisted with artefacts.